Correction: Acid and base dual-controlled cargo molecule release from polyaniline gated-hollow mesoporous silica nanoparticles. Issue 48 (23rd November 2016) - Zhu, Xinyun; Zhao, Jianliang; Wang, Caiqi
Abstract : Correction for 'Acid and base dual-controlled cargo molecule release from polyaniline gated-hollow mesoporous silica nanoparticles' by Xinyun Zhu, et al., Polym. Chem., 2016, 7, 6467–6474.